2021
DOI: 10.1186/s13287-021-02280-2
|View full text |Cite
|
Sign up to set email alerts
|

Sodium alginate-bioglass-encapsulated hAECs restore ovarian function in premature ovarian failure by stimulating angiogenic factor secretion

Abstract: Background Human amniotic epithelial cells (hAECs) exhibit a strong capability to restore ovarian function in chemotherapy-induced premature ovarian failure (POF). However, the therapeutic efficacy of hAECs is usually affected by the limited number and proliferative ability of grafted hAECs in target organs. The transplantation of stem cells encapsulated in sodium alginate-bioglass (SA-BG) composite hydrogel has recently been shown to be an effective strategy for tissue regeneration. The curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Several strategies have been introduced to improve the effectiveness of MSCs, such as the use of sodium alginate-bioglass composite hydrogels and type I collagen as scaffolds during transplantation [ 9 , 10 ]. However, commercialized products widely accepted in clinical practice are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been introduced to improve the effectiveness of MSCs, such as the use of sodium alginate-bioglass composite hydrogels and type I collagen as scaffolds during transplantation [ 9 , 10 ]. However, commercialized products widely accepted in clinical practice are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that BG-containing scaffolds have accelerated cell proliferation and good cell adherence [ 52 , 53 ]. For instance, Jayakumar et al [ 50 ] found that the embedment of BG particles into the Alg hydrogels matrix did not adversely affect the viability and compatibility of MG-63 cells and induced cell attachment and proliferation onto the scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…1 ), and then, the mice were randomly divided into four groups ( n = 10 each group): control group, PBS group, ADSCs group, and MLT-ADSCs group. According to a previous report [ 28 ], mice were intraperitoneally injected with CTX (120 mg/kg, Meilunbio) and busulfan (BUS, 30 mg/kg, Meilunbio) to establish a POI mode. The control group was intraperitoneally injected with an equal volume of 0.9% normal saline.…”
Section: Methodsmentioning
confidence: 99%